Dutch Disease Economics A case Study of Indonesia - Rini Yayuk Priyati (Economic Journal of Emerging Markets, 2011)
The term ‘Dutch disease’ was first used to describe the indirect effects of the boom in the gas sector in the Netherlands in the 1960s on other sectors. This paper applies this framework to analyse the impact of the 2007-2008 surge in oil and gas prices in Indonesia. It finds that this has induced a real appreciation of the Rupiah. In contrast to ‘Dutch disease’ theory, it has been accompanied by growth in agricultural and manufacturing exports. The simulation results suggest that the observed real appreciation due to the booming energy has inhibited the growth of Indonesian exports of agricultural and manufacturing products. Keywords: Dutch disease, energy, agricultural and manufacturing exports